Crete - Ho, Jian Hunt Darren (2019)
Due to the rapid urbanisation in Singapore, most people often felt a disconnect from their environment, in fact, some harbour resentment even. Expanses of lush greenery have turned a pallid grey, paving the way for industrial developments, roads and high-rise buildings. Our Environment, no longer in her original form, is constantly being developed and transformed. Moreover, the fast-paced stressful lifestyle in Singapore has made us live a linear and automated life and few people can afford the time to slow down and appreciate beautiful things around us.